The Effect of Fermentation Time of Waste Cabbage (Brassica oleracea) as a Natural Preservative in Tofu - Deviana Cahyaningsih; Agung Sugiharto (FoodTech: Jurnal Teknologi Pangan, 2022)
Cabbage (Brassica oleracea) is a vegetable commonly grown in the highlands. Cabbage is easily rotten or damaged, so the waste produced by cabbage is in the form of rotten leaves. The waste is a substrate of lactic acid bacteria such as Lactobacillus lactic acid-producing bacteria. Preserving food using chemical preservatives can cause health problems for consumers, so natural preservatives are needed that are safe to use. This study aims to utilize lactic acid produced by fermenting cabbage waste as a tofu preservative. Â Fermentation functions in the formation of lactic acid bacteria from lactose which can slow down decay. The method used in this study was experimental, and the research design was a Completely Randomized Design (CRD) with a fermentation time variation factor consisting of three levels: 4, 7, and 10 days. The study showed that variations in the fermentation time of the fermented cabbage waste solution resulted in a pH ranging from 3-5, and organoleptic observations on tofu preserved with the liquid from fermented cabbage waste were clean white, pale white, and yellow spots. The texture was not slimy, slightly slimy, and slimy. The odor was not pungent or normal, slightly pungent, and pungent. From the research, it can be concluded that the best time for fermentation cabbage waste is 7 to 10 days, with a pH ranging from 3 to 4.Â